HUMAN CAPITAL MANAGEMENT AS AN INTEGRAL PART OF THE STRATEGIC DEVELOPMENT OF AN AGRICULTURAL ENTERPRISE - POLISHCHUK, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the activities of domestic enterprises, the strategic development of human resources involves leveraging critical competencies of employees, i.e., those unique personnel capabilities that create high value and differentiate the organization from competitors to preserve and obtain competitive advantages of the organization, which contribute to increasing organizational efficiency. Managers of modern enterprises need to pay more attention to the role of personnel in the formation and implementation of the activity strategy. The creation of a well-motivated, qualified and capable team, aimed at the full return of its own potential, contributes to the company's achievement of high-performance results and securing a favorable position on the market. Personnel management must correspond to the company's development strategy, protect the interests of employees and ensure compliance with labor legislation in the formation, retention and use of personnel. In addition, focus on the trends and plans for the development of the organization, the achievement of its main goals and consider such aspects as the long-term development of the organization, ensuring the market function of independence, obtaining the qualification of the appropriate dividends, self-financing the development of the enterprise, maintaining financial balance, consolidating the achieved positions in the relevant market. To be of value in human resource management in strategically managed enterprises, a robust human resource management system is crucial. This system ensures the deployment and utilization of appropriate internal and external human resources, providing reassurance about the company's resource management. In order to correctly understand the key functions of the strategic development of the enterprise in the field of management and study of human resources, the personnel management strategy of the enterprise must consist of five aspects (management idea, training system, service certification system, incentive and limitation mechanism, management informatization) based on the perspective of strategy of the enterprise, which is important for the management of the long-term development of the enterprise. The rational deployment, development and application of human resources are the main elements that allow the enterprise to develop better and faster, as well as the key elements for the future development of the enterprise and success in the competition.
Keywords: human capital; agricultural enterprise; development; strategy; management